THE EFFECT OF PRESERVATION METHODE ON THE NUTRITIONAL VALUE AND SHELF LIFE OF SALTED SLEEVE FISH (DECAPTERUS SPP.) IN MUNCAR, BANYUWANGI - Murtiningsih, Ni Made Ayu Meylia; Farida, Iftachul (Proceedings of The Vocational Seminar on Marine & Inland Fisheries, 2026)
Unfortunately, the vast fish potential of Indonesia's marine waters remains underutilized due to limited facilities for handling, storage, processing, and distribution. A further unfortunate consequence is that fishery products are susceptible to quality deterioration. Fishery product processing plays a crucial role in extending shelf life, increasing added value, and maintaining product safety. Indonesia employs various preservation methods, such as salting, smoking, and drying. Each method is examined based on its operating principles, advantages, limitations, and impact on product nutrition. Processing techniques and the implementation of Sanitation Standard Operating Procedures (SSOP) are crucial in increasing the market value of fishery products. Hygiene and appropriate technology are also discussed, supporting both small-scale and modern fishery processing industries. The continued use of traditional methods by many coastal communities is a key factor. Selecting the right processing method can increase product competitiveness, reduce the risk of damage, and support the sustainability of the fisheries sector. The development of fishery technology is highly effective and efficient in maintaining food security and the economy of coastal communities.